Marketing Communication Strategy in the Retail Sector: Examining Repurchase Intention - Yus Hermansyah (Ital Publication, 2024)
In the face of intensifying market competition, the significance of retail marketing strategies and tactics cannot be understated, as they are pivotal in enhancing customers’ satisfaction, fostering loyalty in customers, and ultimately elevating the likelihood of repurchase intentions. This research strives to discern the distinct attributes of customers and gauge their perceptions of the marketing strategies employed by Hypermarket Companies. Additionally, it examines the interplay between customer satisfaction, loyalty, and the consequent cultivation of repurchase intentions. Furthermore, the study explores the foundational retail marketing strategies that underpin the establishment of customer loyalty. The analytical approach encompasses Confirmatory Factor Analysis, SEM-PLS, and Biplot techniques. The findings underscore a customer profile primarily comprising males within the 18–29 age bracket, married, childless, holding undergraduate degrees, enjoying middle-income status, and engaged as private sector employees. Notably, the paramount driver shaping loyalty is the quality of retail service. It is intriguing to note that while the retail mix strategy within Bandung's hypermarkets is predicted to wield no direct influence on loyalty, marketing communication emerges as a potent determinant significantly impacting repurchase intentions. This study contributes to understanding customer behavior and loyalty in hypermarkets. It sheds light on the critical role of service quality in building loyalty. It highlights the importance of effective marketing communication for encouraging repurchase intentions and offers valuable insights for retail marketing strategies. Doi: 10.28991/ESJ-2024-08-01-08 Full Text: PDF